COMPETIÃ‡ÃƒO ENTRE SEIS VARIEDADES DE AMOREIRA (ð˜”ð˜°ð˜³ð˜¶ð˜´ ð˜¢ð˜ð˜£ð˜¢ L.) PARA A PRODUÃ‡ÃƒO DE MASSA VERDE - Campos, AntÃ´nio Rodrigues; Fonseca, AntÃ´nio da Silveira; Abramides, Pedro; Abreu, Oldemar Cardim; Campos, Benedito do EspÃrito Santos de (REVISTA DE AGRICULTURA, 2020)
COMPETIÃ‡ÃƒO ENTRE SEIS VARIEDADES DE AMOREIRA (ð˜”ð˜°ð˜³ð˜¶ð˜´ ð˜¢ð˜ð˜£ð˜¢ L.) PARA A PRODUÃ‡ÃƒO DE MASSA VERDE